Analisis Sistem Akuntansi Kas Kecil Pt Cli Kantor Cabang Surabaya - Prila Safril Ataladin Madani; Fahmi Poernamawatie; Mitha Endah Aprilia (AKUNTANSI 45, 2024)
PT Combi Logistics Indonesia (CLI) Surabaya branch office is engaged in export-import transportation services. Implementing a petty cash accounting system helps the company run conductively. Thus there are no conditions in the company's financial management. The research aims to determine the company's petty cash accounting system analysis. The qualitative research type used is observation, interview, and data documentation data collection procedures. Data analysis techniques are data reduction, presentation, and conclusion. The research results show that the petty cash accounting system function is not running well because the cash function, accounting function, and operational function (users of petty cash funds) are one. So there are problems: duplicate work, accountability summary, and authorization. The subsequent research result forms related to the petty cash accounting system have been implemented. However, there has been no evaluation regarding their effectiveness. The next research result was that the company had carried out journal reporting for 2 years because it was only a branch office, and subsequent reporting was carried out by the central finance department.